Zabijanie opowieści. Dyskurs kanibalistyczny w historii i literaturze ludu Basotho - van Wyk, Johan (Er(r)go. Teoria - Literatura - Kultura, 2003)
Johann van Wyk Killing a Story: The Discourse of Cannibalism in the History and Literature of the Basotho This essay explores the theme of cannibalism in the historical and literary textsrelating to the Basotho. It points to the link between cannibalism and the historical period the lifaqane. which was an heroic epoch gone out of control. It show how the repression of cannibalism is inscribed in the founding moment of the Basotho nation. Therefore how it is linked to Basotho identity. Another aspect explored is the link between cannibalism and the supernatural (the use of human flesh in medicine and ritual). but also how cannibalism was used as a literary motif by the SeSotho within the contesting ideologies of traditional SeSotho world views and Christianity. Itfurther touches on the problem of the historicity and factuality of cannibalism. as well as its link to the mouth as performative instrument in story telling.